UJI RESISTENSI Salmonella typhi DARI PENDERITA DEMAM TIFOID TERHADAP BEBERAPA ANTIBIOTIK - Riyan Sukma; Cut Indriputri; Nurgazali Nurgazali; Jumhur Salam (Universitas Cokroaminoto Palopo, 2023)
Typhoid fever is a systemic infection caused by Salmonella typhi. This study aims to determine the resistance test of Salmonella typhi bacteria from typhoid fever sufferers to several antibiotics. Typhoid fever patient blood samples were taken from two hospitals in Makassar City, namely Labuang Baji Hospital and Makassar City Hospital. Samples were inoculated on SSA media (Salmonella shigella Agar). Then gram staining and biochemical tests and sugar tests were carried out. Sensitivity test using the Agar Disc Diffusion method. The results obtained were that of the 98 samples taken, only 30 samples met the inclusion criteria. The results of the sensitivity test using the Disc Diffusion Agar method showed that 21 samples were resistant to Ciprofloxacin, 1 sample was resistant to Chloramphenicol and 8 samples were resistant to Amoxicillin.